Genome-wide analysis of dental caries and periodontitis combining clinical and self-reported data - Dmitry Shungin (Nature Portfolio, 2019)
Dental caries and periodontitis are among the most common medical conditions. Here, the authors report a GWAS for measures of oral health that reveals 47 risk loci for caries, find genetic correlation with 31 other complex traits and use Mendelian randomization analyses to explore potential causal relationships.